Tooth Shape Research and Contour Machining of Hirth Coupling - Shao Guangjun; Li Gang; Ruan Wenhao (Jixie chuandong)
The hirth coupling is widely used in the centrifugal air compressor unit due to its characteristic of high torque capacity and self centering etc.It is aimed at deriving the accurate calculating formulas of hirth tooth shape,to provide accurate parameters for the hirth forming grinding.